Demand for and availability of online support to stop smoking - Beatriz Helena Carlini; Telmo Mota Ronzani; Leonardo Fernandes Martins; Henrique Pinto Gomide; Isabel Cristina Weiss de Souza (Universidade de São Paulo, 2012)
OBJECTIVES: Estimate the frequency of online searches on the topic of smoking and analyze the quality of online resources available to smokers interested in giving up smoking. METHODS: Search engines were used to revise searches and online resources related to stopping smoking in Brazil in 2010. The number of searches was determined using analytical tools available on Google Ads; the number and type of sites were determined by replicating the search patterns of internet users. The sites were classified according to content (advertising, library of articles and other). The quality of the sites was analyzed using the Smoking Treatment Scale- Content (STS-C) and the Smoking Treatment Scale - Rating (STS-R). RESULTS: A total of 642,446 searches was carried out. Around a third of the 113 sites encountered were of the 'library' type, i.e. they only contained articles, followed by sites containing clinical advertising (18.6) and professional education (10.6). Thirteen of the sites offered advice on quitting directed at smokers. The majority of the sites did not contain evidence-based information, were not interactive and did not have the possibility of communicating with users after the first contact. Other limitations we came across were a lack of financial disclosure as well as no guarantee of privacy concerning information obtained and no distinction made between editorial content and advertisements. CONCLUSIONS: There is a disparity between the high demand for online support in giving up smoking and the scarcity of quality online resources for smokers. It is necessary to develop interactive, customized online resources based on evidence and random clinical testing in order to improve the support available to Brazilian smokers.